The neutrophil-to-lymphocyte ratio is associated with all-cause and cardiovascular mortality among individuals with hypertension - Xuexue Zhang; Rui Wei; Xujie Wang; Wantong Zhang; Mengxuan Li; Tian Ni; Weiliang Weng; Qiuyan Li (Cardiovascular Diabetology, 2024)
Abstract Background Identifying reliable prognostic markers is crucial for the effective management of hypertension. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential inflammatory marker linked to cardiovascular outcomes. This study aims to investigate the association of NLR with all-cause and cardiovascular mortality among patients with hypertension. Methods This study analyzed data from 3067 hypertensive adults in the National Health and Nutritional Examination Surveys (NHANES) from 2009 to 2014. Mortality details were obtained from the National Death Index (NDI). Restricted cubic spline (RCS) was deployed to visualize the association of the NLR with mortality risk. Weighted Cox proportional hazards models were employed to assess the independent association of NLR with mortality risk. Time-dependent receiver operating characteristic curve (ROC) analysis was conducted to access the predictive ability of NLR for survival. Mediation analysis was used to explore the indirect impact of NLR on mortality mediated through eGFR. Results Over a median 92.0-months follow-up, 538 deaths occurred, including 114 cardiovascular deaths. RCS analysis revealed a positive association between NLR and both all-cause and cardiovascular mortality. Participants were stratified into higher (> 3.5) and lower (≤ 3.5) NLR groups. Weighted Cox proportional hazards models demonstrated that individuals with higher NLR had a significantly increased risk of all-cause (HR 1.96, 95% confidence interval (CI) 1.52–2.52, p < 0.0001) and cardiovascular mortality (HR 2.33, 95% CI 1.54–3.51, p < 0.0001). Stratified and interaction analysis confirmed the stability of the core results. Notably, eGFR partially mediated the association between NLR and both all-cause and cardiovascular mortality by a 5.4% and 4.7% proportion, respectively. Additionally, the areas under the curve (AUC) of the 3-, 5- and 10- year survival was 0.68, 0.65 and 0.64 for all-cause mortality and 0.68, 0.70 and 0.69 for cardiovascular mortality, respectively. Conclusion Elevated NLR independently confers an increased risk for both all-cause and cardiovascular mortality in individuals with hypertension.